Education And Training Centre At Science And Techno Park USU Kwala Bekala - Nasution, Achmad Delianur; Puteri, Shafira Najwa (Talenta Publisher, 2020)
Education and Training Center is a place where all activities to give, obtain, improve, and develop work competencies, productivity, discipline, attitude, and work ethic at a certain level of skills and expertise by the qualifications of a job or a job. (UU RI, 2003). The method is to create an Education and Training Centre. Education and Training center society as informal education in improving competence or quality for individuals. The Education and Training center is one of the most important buildings in the USU Kwala Bekala Campus. The USU Kwala Bekala campus divided into several zones. The entrance zone is the main gate that describes the initial image of the USU Kwala Bekala campus. This zone designed with the concept of Science & Technology Park. Because the site location located in the entrance zone, the building design as